Time-harmonic dynamical stress field in a system comprising a pre-stressed orthotropic layer and pre-stressed orthotropic half-plane - Akbarov, Surkay; Ilhan, Nihat (SPRINGER, 2010)
The time-harmonic dynamical stress field in a system comprising a pre-stressed orthotropic layer and orthotropic half-plane is studied within the scope of the piecewise homogeneous body model utilizing the three-dimensional linearized theory of elastic waves in an initially stressed body. The main focus is on the influence of the mechanical properties of the constituent materials and the initial stresses present on the resonance values of the normal stress acting on the interface plane and on the resonance values of the frequency of the external point-located force. The numerical results are presented and discussed. In particular, it is shown that the values of the normal stress decrease with a decrease in the modulus of elasticity of the materials along the thickness of the covering layer.
Keywords: Time-harmonic dynamical stress field; Initial stress; Orthotropic material; Frequency; Resonance; PROPAGATION; SURFACE; SLAB; Mechanics